Neem (Azadirachta indica): A Review on Medicinal Kalpavriksha - Reddy, I. V. Srinivasa; Neelima, P. (International Journal of Economic Plants, 2022)
Neem, has thrown the light worldwide in recent years, due to its wide range of medicinal properties. The tree has been largely used in Naturopathy, Unani and Homoeopathic medicine and has become a lodestar of current medicine. Further it elaborates a vast array of biologically active compounds that are chemically diverse and structurally complex. More than 150 compounds have been isolated from different parts of neem and these have been divided into two major classes isoprenoids and non-isoprenoids, which are proteins and carbohydrates. Further, it consists of sulphurous compounds, polyphenolic compounds such as flavonoids and their glycosides, dihydrochalcone, coumarin, tannins and aliphatic compounds. All parts of the neem tree viz., leaves, flowers, seeds, fruits, roots and bark have been used traditionally for the treatment of inflammation, infections, fever, skin diseases, dental disorders, etc. Every part of the neem tree viz., roots, seeds, flowers, bark, leaves, fruit pulp and its constituents have been demonstrated to exhibit immune modulatory, anti-inflammatory, anti hyperglycaemic, antiulcer, antimalarial, antifungal, antibacterial, antiviral, antioxidant, antimutagenic, antidiabetic and anticarcinogenic properties.